Effects of Simulated and Profound Unilateral Sensorineural Hearing Loss on Recognition of Speech in Competing Speech. Issue 2 (March 2020) - Asp, Filip; Reinfeldt, Sabine
Abstract : Objectives: Unilateral hearing loss (UHL) is a condition as common as bilateral hearing loss in adults. Because of the unilaterally reduced audibility associated with UHL, binaural processing of sounds may be disrupted. As a consequence, daily tasks such as listening to speech in a background of spatially distinct competing sounds may be challenging. A growing body of subjective and objective data suggests that spatial hearing is negatively affected by UHL. However, the type and degree of UHL vary considerably in previous studies. The aim here was to determine the effect of a profound sensorineural UHL, and of a simulated UHL, on recognition of speech in competing speech, and the binaural and monaural contributions to spatial release from masking, in a demanding multisource listening environment. Design: Nine subjects (25 to 61 years) with profound sensorineural UHL [mean pure-tone average (PTA) across 0.5, 1, 2, and 4 kHz = 105 dB HL] and normal contralateral hearing (mean PTA = 7.2 dB HL) were included based on the criterion that the target and competing speech were inaudible in the ear with hearing loss. Thirteen subjects with normal hearing (19 to 60 years; mean left PTA = 4.1 dB HL; mean right PTA = 5.5 dB HL) contributed data in normal and simulated "mild-to-moderate" UHL conditions (PTA = 38.6 dB HL). The main outcome measure was the threshold for 40% correct speech recognition in colocated (0°) and spatially and symmetrically separated (±30° and ±150°) competing speech conditions. Spatial release from masking was quantified as the threshold difference between colocated and separated conditions. Results: Thresholds in profound UHL were higher (worse) than normal hearing in separated and colocated conditions, and comparable to simulated UHL. Monaural spatial release from masking, that is, the spatial release achieved by subjects with profound UHL, was significantly different from zero and 49% of the magnitude of the spatial release from masking achieved by subjects with normal hearing. There were subjects with profound UHL who showed negative spatial release, whereas subjects with normal hearing consistently showed positive spatial release from masking in the normal condition. The simulated UHL had a larger effect on the speech recognition threshold for separated than for colocated conditions, resulting in decreased spatial release from masking. The difference in spatial release between normal-hearing and simulated UHL conditions increased with age. Conclusions: The results demonstrate that while recognition of speech in colocated and separated competing speech is impaired for profound sensorineural UHL, spatial release from masking may be possible when competing speech is symmetrically distributed around the listener. A "mild-to-moderate" simulated UHL decreases spatial release from masking compared with normal-hearing conditions and interacts with age, indicating that small amounts of residual hearing in the UHL ear may be more beneficial for separated than for colocated interferer conditions for young listeners.